Polska, losy panstwa i narodu - Samsonowicz, Henryk; Samsonowicz, Henryk; Tazbir, Janusz; Lepkowski, Tadeusz; Nalecz, Tomasz (Warszawa : Iskry, 1992)
A concise history of Poland from its early rise up to 1939, including its religious, social and industrial growth.
Narodziny panstwa i narodu / Henryk Samsonowicz -- Rzeczpospolita wielu narodow / Janusz Tazbir -- Narod bez panstwa / Tadeusz Lepkowski -- Odzyskana niepodleglosc / Tomasz Nalecz.
Includes bibliographical references (p. 585-[586]) and indexes.
Keywords: Poland -- History